Study of titanium oxidation kinetics at temperature above polymorphic transformation - Trush, Vasyl; Luk’yanenko, Alexander; Fedirko, Viktor (Technology audit and production reserves, 2021)
The object of research is the analytical description of the phenomena in the near-surface layer, which are caused by the interaction of titanium with oxygen at high temperatures. These are temperatures that exceed the polymorphic transformation of the metal. High-temperature oxidation gives titanium products unique performance properties. Of course, such characteristics are determined, first of all, by the state of the near-surface layer. Therefore, an understanding of oxidation processes will make it possible to predict the state of the near-surface layer after heat treatment. However, to date, no unified approach has been created to describe the mechanism and kinetics of high-temperature oxidation of titanium in the near-surface layer. Indeed, most of the existing approaches make it possible to predict the nature of oxidation in the bulk of the metal. Some scientific papers describe the kinetics of oxidation, taking into account only the formation and growth of oxide layers. However, simultaneously with oxide formation, a diffusion zone is formed, which significantly affects the kinetics. Therefore, today one of the most problematic areas of high-temperature titanium oxidation is the description of the processes that take place in the near-surface layer. In this work, to describe the kinetics of high-temperature oxidation of titanium, in addition to the formation and growth of the oxide layer, the formation and growth of the diffusion zone is taken into account. In the diffusion zone, under the influence of structural phase transformations, solid solutions of oxygen are formed in the alpha and beta phases. This approach made it possible to take into account additional factors and thereby more accurately describe the processes of high-temperature oxidation of titanium. As a result of the calculations, the thickness of the oxide layer of the diffusion zone is given depending on the oxygen concentration and the duration of treatment. And also the dependences of the kinetics of displacement of the boundary of the oxide-diffusion layer are given and a system of equations for calculating the ratio of the formed phase components is developed. Thanks to the proposed analytical approach, it will be possible to calculate the sizes of interphase boundaries on the basis of temperature-time parameters and oxygen concentration and thereby form a hardened near-surface layer with certain functional properties